Silencing of LRRFIP1 reverses the epithelial–mesenchymal transition via inhibition of the Wnt/β-catenin signaling pathway. Issue 1 (28th August 2015) - Douchi, Daisuke; Ohtsuka, Hideo; Ariake, Kyohei; Masuda, Kunihiro; Kawasaki, Shuhei; Kawaguchi, Kei; Fukase, Koji; Oikawa, Masaya; Motoi, Fuyuhiko; Naitoh, Takeshi; Katayose, Yu; Egawa, Shinichi; et al.
Highlights: The role of LRRFIP1 in the EMT and invasion of carcinoma cells was investigated. Repression of LRRFIP1 caused reversal of EMT and inhibited migration and invasion. Silencing of LRRFIP1 regulated phosphorylation and nuclear localization of β-catenin. β-catenin expressed on the membrane was increased in LRRFIP1 silenced cancer cells. Abstract: The canonical Wnt/β-catenin signaling pathway has been shown to promote the epithelial–mesenchymal transition (EMT), which is a crucial process in multiple embryonic developmental processes and the progression of carcinomas. We recently provided evidence that leucine-rich repeat flightless-1-interacting protein 1 (LRRFIP1) promotes cancer metastasis and invasion. In the present study, we identified the signaling elements targeted by LRRFIP1 for promotion of the EMT in pancreatic and lung cancer. LRRFIP1 silencing reversed the EMT, as shown by increased expression of E-cadherin (an epithelial marker) and decreased expression of vimentin (a mesenchymal marker). Silencing of LRRFIP1 up-regulated phosphorylation of β-catenin and decreased its nuclear localization by targeting the β-catenin destruction complex. The expression of β-catenin and E-cadherin in the plasma membrane fraction was increased in LRRFIP1 silenced cancer cells, and the migration and invasion capabilities were strongly inhibited. In addition, this protein was highly expressed at the invasion front of malignant tissue collected from pancreatic cancer patients. Consequently, our data strongly suggested that LRRFIP1 played an important role in the invasion of carcinoma cells. Our data provide experimental evidence that LRRFIP1 is an attractive candidate for targeted therapy in human cancers.